Measuring the Ultrafast Spectral Diffusion Dynamics of Colloidal CdSe Nanomaterials. (23rd January 2019) - Do, Thanh Nhut; Zhang, Cheng; Ong, Xuanwei; Lian, Jie; Chan, Yinthai; Tan, Howe-Siang
Abstract: We use ultrafast coherent two-dimensional electronic spectroscopy (2DES) to study the ultrafast spectral diffusion dynamics of colloidal CdSe quantum dots (QDs) and CdSe nanoplatelets (NPLs). The Center Line Slope (CLS) and Nodal Line Slope (NLS) techniques were employed to analyse the 2DES spectra. We show that no spectral diffusion dynamics occurs for the CdSe QDs. On the other hand, spectral diffusion was observed in the CdSe 5 mono-layers NPLs heavy-hole transition. The normalized Frequency Fluctuation Correlation Function (FFCF) of the CdSe NPLs heavy-hole transition was measured to have a major fast decay component at 140 fs.